A folk divided : homeland Swedes and Swedish Americans, 1840-1940 - Barton, H. Arnold (Hildor Arnold), 1929-2016 (Southern Illinois University Press, 1994)
"In this unique longitudinal study of how a divided people relate to one another, H. Arnold Barton outlines dilemmas created by the great migration of Swedes to the United States from 1840 through 1940 and the complex love-hate relationship that resulted between those who stayed and those who left. During that hundred-year period, one Swede out of five voluntarily immigrated to the United States, and four-fifths of those immigrants remained in their new country. This study seeks to explore the far-reaching implications of this mass migration for both Swedes and Swedish Americans."--Jacket